Handbuch globale Handelsräume und Handelsrouten: von der Antike bis zur Gegenwart - Häberlein, Mark; Denzel, Markus A.; Berger, Markus; Borell, Brigitte; Christ, Georg; Denzel, Markus A.; Depkat, Volker; Ewert, Ulf Christian; Keese, Alexander; Lang, Heinrich; Marx, Christoph; Mückler, Hermann; et al. (De Gruyter Oldenbourg, 2024)
This handbook is the first in German to give an overview of the most important trading regions and trade routes since antiquity. It takes flows of goods and maritime and continental trade routes into account, as well as climate and geographical circumstances, central actors, and significant infrastructure. At the same time, it synthesizes international research on various major regions
Keywords: Aufsatzsammlung; Geschichte; Wegenetz; Handelsstraße; Fernhandel; Welthandel